GEJALA DAN INTENSITAS SERANGAN HAMA KUTU DAUN (Chaetosiphon sp) PADA TANAMANSTROBERIDI KELURAHAN RURUKAN KOTA TOMOHON - Zainudin Limbanadi; Juliet M.E. Mamahit; Christina L. Salaki; Guntur S.J. Manengkey (COCOS, 2015)
ABSTRACTStudy aims to determine the symptoms and the intensity of aphids the strawberry (Chaetosiphon sp) were held in the Village Rurukan Tomohon. This study was conducted over four months from February to May 2014. Study uses survey and observations of aphids and deliberate sampling on strawberry plants were observed.Field research was conducted in the area of planting strawberries and laboratory observations carried out at the Laboratory of Entomology and Plant Pests Faculty of Agriculture, University of Sam Ratulangi. Subplot observation intensity of the attacks on strawberry crop land has a length of 2 m and a width of 1 m to 12 m long beds. In each of the beds made two subplots, each subplot were taken 20 plants.The results showed that the strawberry aphids (Chaetosiphon sp) affects plant growth both in the vegetative and generative phase of the insect in the vegetative phase of the plants become stunted, and attacks on the generative phase led to the formation of flowers and fruit inhibited. Average intensity of the attacks in of strawberry aphidsRurukan Tomohon increased every week with the highest intensity in the sixth week, namely 46.0% plants affected in the first observation and 55.0% plants affected in the second observation.Keywords: Symptoms, attack intensity, Chaetosiphon sp.